(untitled) (Economics and region, 2018)
The problems of reforming the tourism distribution are under consideration. The necessity of implementing innovation in the tourism information management system as a guarantor of its competitiveness is substantiated. The prospects of the integration of innovative information system and the distribution channels are determined